ANALYSING EMPLOYEE DEVELOPMENT STRATEGIES THROUGH HRM LITERATURE REVIEW - Hartati Maango; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
The analysis of employee development strategies in the Human Resource Management (HRM) literature review highlights the importance of a comprehensive and systematic approach in maintaining organisational competitiveness and growth. Findings show that full support from top management, alignment with organisational goals, and appropriate training programme design are crucial factors. In addition, an organisational culture that supports continuous learning and innovation is considered important in promoting effective employee development. Diverse training methods, such as e-learning, mentoring and hands-on training, can enhance the effectiveness of employee development. Continuous evaluation and follow-up of development programmes are also important to ensure optimal application of skills and knowledge in daily work. Overall, employee development not only contributes to individual growth but also improves overall organisational performance, creates competitive advantage, and prepares the organisation to face future challenges.